Efeitos ambientais e genéticos sobre o desempenho pré e pós desmama em bovinos Nelore na Região Sul do Brasil - Souza, Paulo Rodrigo Santos de (2005)
The objective of this study was to verify the effect of environmental factors and to estimate genetic parameters for weight characteristics, observed before and after weaning, in Nellore breed cattle in the South Region of Brazil. The data analyzed came from animals created in the States of Rio Grande do Sul, Santa Catarina and Paraná and were collected from 1976 to 2001 (26 years). With the objective of to improve the accuracy, they were eliminated from the original file, observations from sires with progeny smaller than five sons and herds with less than twenty observations. They were estimated genetic parameters for weight at birth (PN), weaning weight adjusted to 205 days of age (P205), in paper 01; for weight adjusted to 365 and 550 days of age (P365 and P550, respectively), paper 02 and, for average daily weight gain from birth to 205 days of age (GPND) and from 205 to 550 days of age (GPDS), paper 03. In paper 01, it was studied the environmental effect on PN and P205. For that, it were used 13,387 records from Nellore breed animals, 6,486 males and 6,901 females, sired by 431 bulls by Controle de Desenvolvimento Ponderal (CDP), by Associação Brasileira de Criadores de Zebu. It was realized an analyze of variance by GLM (SAS, 2001) to verify which environmental effects statically influenced PN and P205. For PN they were significant the effects of herd, year of birth and sex, and for P205, they were significant the effects of herd, year and season of birth, sex, management conditions, feeding system. The estimated (co)variance components used to estimate the genetic parameters were obtained by Restricted Maximum Likelihood Method using the program MTDFREML (Boldman et al., 2001) and adopting an animal model. The heritability coefficients estimated for the additive genetic direct and maternal effects, and the correlation coefficient between them, were .56 ± .04; .23 ± .03 and -.85 ± .03, for PN and .64 ± .05; .38 ± .04 and -.77 ± .03 for P205, respectively. The results suggest that it is possible to select the studied Nellore herds by pre-weaning characteristics and to get considerable gain. In paper 02 they were analyzed records on 11,823 animals for P365 and 10,884 animals for P550. The statistical significant environmental effects on the studied weight characteristics, were evaluated by an analyze of variance, by GLM (SAS, 2001). The (co)variance components were estimated by Restricted Maximum Likelihood using the MTDFREML program (Boldman et al., 2001). The animal model for P365, considered the fixed effects of herd , year and season of birth, sex and feeding system, and as a covariable, the age of the cow at parturition, and the random effects additive genetic direct and maternal and the environment permanent effect. For P550, the model was the same, only including the fixed effect of season of birth. The observed averages were 249.92 ± 61.37 kg and 335.79 ± 94.37 kg, and the estimated heritability direct and maternal coefficients were .66 ± .05 and .11 ± .03 and, .57 ± .04 and .07 ± .03, respectively for P365 and P550, suggesting that selection for both the weights will produce genetic progress. The genetic correlation between P365 and P550 was high (.64), suggesting that it is possible to anticipate the selection for one year of age with almost the same results that those obtained with the selection at 550 days of age. In paper 03, they were used records on 13,387 (GPND) and 10,884 (GPDS) Nellore breed animals. It was realized an analyze of variance by GLM (SAS, 2001) to identify the environmental effects statistical significant, to be including in the model to estimate the genetic parameters by M1 which considered as fixed the effects of State, herd, year and season of birth, sex, feeding system, management conditions, and, as a covariable, the age of the cow at birth. For GPND, were not statistically significant the effects of State and age of the cow at birth; GPDS was statistically influenced by herd, year, feeding system and sex. The (co)variance components, used to estimate the genetic parameters, were obtained by Restricted Maximun Likelihood Method, using an animal model considering the significant fixed effects in M1 and, as random, the additive genetic direct and maternal effects and the environment permanent effect. The averages were .709 ± .16 kg (GPND) and .463 ± .22 kg (GPDS), the heritability coefficients were .33 ± .05 and .04 ± .04 and .19 ± .04 and .05 ± .03, respectively for direct and maternal effects for GPND and GPDS. The correlation coefficient between GPND and GPDS was .45, suggesting that the selection for GPND will improve GPDS